(untitled) (Research Nepal Journal of Development Studies, 2021)
English medium of instruction in multilingual science classes: teaching science or language? is an attempt to identify the effects, methods, and approaches of teaching science in English medium of instruction in Multilingual (ML) science classes. The article is prepared on the basis of in-depth interviews taken with science teachers who are teaching science in multilingual classes. Three science teachers are selected purposively from different three (English Medium Instructions) EMI schools of Kathmandu valley. After taking the interview it was transcribed, coded, and generated the theme. Based on the themes generated it was found that the EMI is important for teaching and learning but it is not everything. Similarly, it was found that the teaching of science is not similar to teaching the grammar structures, and always not possible to use English as a medium of making the concept clear of theoretical ideas of science.